Drone perching control - Yan, Daryl ZhenYu (Nanyang Technological University, 2024)
The evolution of drone technology has led to various industries adapting the use of drones, due to their adaptability and agility. Quadcopter drones are highly agile, versatile, and adaptable thus, they have been deployed in various fields like agriculture and surveillance. However, their operational endurance is often constrained by onboard battery capacity, particularly during surveillance missions requiring prolonged hovering. There have been several hardware enhancements developed to address this limitation, and perching mechanisms have emerged as one of the most promising. However, most of the perching mechanisms are non-passive systems which consumes power from the on-board battery to operate. The objective of this project is to explore different solutions using gear design and 3D modeling to develop both passive and semi-passive perching mechanism such as the Weight-Based Gripper and the Servo Assisted Gripper respectively. Thereby, allowing quadcopters to securely perch on branches, light poles, and other suitable surfaces, enhancing the efficiency of surveillance missions and terrain surveying operations while also reducing the chances of detection through noise reduction.